Antibiotic-induced disruption of the microbiome exacerbates chemotherapy-induced diarrhoea and can be mitigated with autologous faecal microbiota transplantation. (August 2021) - Wardill, Hannah R.; van der Aa, Stijn A.R.; da Silva Ferreira, Ana R.; Havinga, Rick; Tissing, Wim J.E.; Harmsen, Hermie J.M.
Abstract: Background: Chemotherapy is well documented to disrupt the gut microbiome, leading to poor treatment outcomes and a heightened risk of adverse toxicity. Although strong associations exist between its composition and gastrointestinal toxicity, its causal contribution remains unclear. Our inability to move beyond association has limited the development and implementation of microbial-based therapeutics in chemotherapy adjuncts with no clear rationale of how and when to deliver them. Methods/Results: Here, we investigate the impact of augmenting the gut microbiome on gastrointestinal toxicity caused by the chemotherapeutic agent, methotrexate (MTX). Faecal microbiome transplantation (FMT) delivered after MTX had no appreciable impact on gastrointestinal toxicity. In contrast, disruption of the microbiome with antibiotics administered before chemotherapy exacerbated gastrointestinal toxicity, impairing mucosal recovery ( P < 0.0001) whilst increasing diarrhoea severity ( P = 0.0007) and treatment-related mortality ( P = 0.0045). Importantly, these detrimental effects were reversed when the microbiome was restored using autologous FMT ( P = 0.03), a phenomenon dictated by the uptake and subsequent expansion of Muribaculaceae. Conclusions: These are the first data to show that clinically impactful symptoms of gastrointestinal toxicity are dictated by the microbiome and provide a clear rationale for how and when to target the microbiome to mitigate the acute and chronic complications caused by disruption of the gastrointestinal microenvironment. Translation of this new knowledge should focus on stabilising and strengthening the gut microbiome before chemotherapy and developing new microbial approaches to accelerate recovery of the mucosa. By controlling the depth and duration of mucosal injury, secondary consequences of gastrointestinal toxicity may be avoided. Highlights: MTX is associated with disruption of the gut microbiome secondary to mucosal injury. Antibiotics increase MTX-induced diarrhea and mortality by impairing mucosal recovery. FMT is able to restore the microbiome after MTX and antibiotics. FMT minimises detrimental effects of antibiotics when delivered prior to MTX.